Incidence and baseline characteristics of relapse or exacerbation in patients with pulmonary sarcoidosis in Japan: Pulmonary sarcoidosis baseline risk factors for long-term outcome in Japan - Murata, Okinori; Suzuki, Katsuya; Takeuchi, Tsutomu; Kudo, Atsuko (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2021)
Background: To identify the incidence and baseline characteristics of relapse and exacerbation in patients with pulmonary sarcoidosis over a long-term period.Methods: We enrolled 103 patients. The incidence and characteristics of relapse or exacerbation were prospectively recorded and statistically analysed.Results: Of 103 patients, 79% were women. Mean age at diagnosis was 50.1 ± 16.4 y. Mean observation period was 9.8 ± 8.6 y. Overall relapse or exacerbation was 22.3% (n = 23) and mean time from diagnosis (including diagnosis of ocular disease at another facility) to relapse or exacerbation was 8.7 ± 8.3 y. We analysed the data of 69 patients who were observed for > 5 y and identified relapse or exacerbation within 5 y in 9 patients. Comparison of characteristics at diagnosis between the relapse/exacerbation group and the improved/stable group showed that the relapse/exacerbation group had a significantly higher frequency of bilateral hilar lymphadenopathy, longer disease duration, ocular involvement, cardiac involvement, and oral glucocorticoid use at diagnosis (P = 0.014, 0.027, 0.019, 0.035, and 0.0043, respectively). The number of risk factors was positively and significantly associated with the cumulative rate of relapse/exacerbation (P = 0.048).Conclusion: Our long-term observational cohort study newly identified the incidence and baseline risk factors for relapse or exacerbation in patients with pulmonary sarcoidosis over a long-term period. Scoring the number of factors at baseline may facilitate the prediction of relapse or exacerbation.